PENGARUH KOMPENSASI FINANSIAL, HUBUNGAN KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH PARKIR KOTA DENPASAR - boru situngkir, sari agustia (E-Jurnal Manajemen; Vol 2 No 8 (2013), 2013)
This study aimed to determine the effect of financial compensation, labor relations and the physical work environment affects the performance of the employee parking PD Denpasar. Respondents in the study a number of 62 employees PD parking Denpasar. Proportionate random sampling method is used to take a sample. Data analysis with multiple linear regression techniques. The analysis showed that simultaneous and partial financial compensation, labor relations and the physical work environment affects the performance impact on employee performance. Employment variable is said to be the most dominant variables affecting employee performance. The company should be increased support among fellow employees in completing the work. Keywords: financial compensation, labor relations, physical work environment, and performance